2017
DOI: 10.1016/j.rhisph.2017.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere engineering: Enhancing sustainable plant ecosystem productivity

Abstract: The rhizosphere is arguably the most complex microbial habitat on earth, comprising an integrated network of plant roots, soil and a diverse microbial consortium of bacteria, archaea, viruses, and microeukaryotes. Understanding, predicting and controlling the structure and function of the rhizosphere will allow us to harness plantmicrobe interactions and other rhizosphere activities as a means to increase or restore plant ecosystem productivity, improve plant responses to a wide range of environmental perturba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
150
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(154 citation statements)
references
References 144 publications
3
150
0
1
Order By: Relevance
“…Our field results were validated with a greenhouse experiment where we grew a subset of the plant genotypes in both autoclaved (sterilized) soil and unsterilized soil directly from the Carrington field. Greenhouse experiments in unsterilized (native) field soil showed similar results to field conditions, but in sterilized soil resistant plant genotypes performed much worse in the Sclerotinia assay, to the extent that nearly all resistance was eliminated, thus adding to the data that a healthy rhizosphere plays an important role in a plant's ability to resist infection [45][46][47] .…”
Section: Discussionmentioning
confidence: 77%
“…Our field results were validated with a greenhouse experiment where we grew a subset of the plant genotypes in both autoclaved (sterilized) soil and unsterilized soil directly from the Carrington field. Greenhouse experiments in unsterilized (native) field soil showed similar results to field conditions, but in sterilized soil resistant plant genotypes performed much worse in the Sclerotinia assay, to the extent that nearly all resistance was eliminated, thus adding to the data that a healthy rhizosphere plays an important role in a plant's ability to resist infection [45][46][47] .…”
Section: Discussionmentioning
confidence: 77%
“…As shown in Figures 2-5, in most cases, the effluent quality was further improved by the presence of vegetation. Some studies reported that the role of aerobic bacteria such as Rhizosphere in the uptake of nutrients (phosphate and nitrate) and oxygen transport is effective (22)(23)(24)(25). Several biological and physicochemical reactions are involved in the transformation of nitrogen into different biologically useful forms.…”
Section: Discussionmentioning
confidence: 99%
“…Organic carbon substrates and phosphorus compounds exhibit enormous ranges and are persistent abiotic stressors affecting microbial survival and growth in soils [49]. However, carbon and phosphorus limitation in the rhizosphere can be alleviated by root exudates and soil pH neutralization [50]. Decreased nitrogen availability in the rhizosphere also induces microbial DON stress16.…”
Section: Community Assembly Mechanisms Of C Sinensis Microbiomes Fromentioning
confidence: 99%